Les codes et les faits: l'article 170 du Code criminel - St-Pierre, Paul (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
The difficulties which the interpretation of article 170 of the Criminal Code raises are to a large extent the result of the role language plays in legal discourse, as an intermediary between the legal text and the facts to which it must apply. While language makes possible — through its referential function — the application of the text to particular situations, it also introduces ambiguity into the legal text and leads to the need for interpretation.